CREENCIAS Y PRÁCTICAS DE LAS MADRES RELACIONADAS CON LOS SIGNOS Y SÍNTOMAS EN LA ERUPCIÓN DENTAL DE SUS HIJOS/AS (2010)
Objective: To establish the beliefs of mothers of children related to the process of tooth eruption and to identify associated systemic manifestations as normal to them in this process.Methods: A cross-sectional study was done. A sample was conformed by 87 mothers of infants who were part of the nursery, toddlers and preschool Centro Infantil Biberones of Bucaramanga. Data were collected through a questionnaire administered to these mothers. For the analysis, statistical tests Chi2 and Student’s t test were done (α < 0.05).Results: Thirty nine percent of the mothers associated teething with clinical manifestations. It was observed that increasing the desire to bite was the most frequent (75.9%). Similarly, it was established that the behavior most often used by mothers to relieve the symptoms of their children is to put the pacifier (78.2%).Conclusions: This study allowed us to establish the consolidated knowledge and practices based on existing references and related information reported by mothers.